(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As thePinned Rigid connections will not give real behavior of the structure so partial restrained connection are introduced in the structure by introducing spring stiffness to achieve the approximately real behavior of structure. In this paper analysis and design of top seat angle connection is presented and beam-column behavior for maximum deflection joint displacement are compared with different load combination for unsymmetrical structure. The results are taken from Staad-pro v8i and designed values are used to calculate relative spring stiffness of beam-column joint and applied on structure to get the semi-rigid type of connection and results are discussed for all three types of connections called pinned, rigid semi-rigid connection.